2013
DOI: 10.1108/18363261311314935
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of research students' writing support intervention

Abstract: Purpose-Achieving quality standards in postgraduate education, particularly among Higher Degree by Research (HDR) students, can be challenging. In addition to the diverse educational and cultural backgrounds of these students, thesis writing frequently involves the development of new skills associated with the comprehension of a large volume of information, critical analysis and the development of an academic writing style. Many students need support in one or all of these key areas. Universities currently pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…Consistent with the positive perceptions of consultations services reported in previous research (Bell, 2000;Berry et al, 2012;O'Mahony et al, 2013), data gathered in this study pointed to highly positive perceptions of the consultations service. Questionnaire data showed 99% of 216 respondents stating they would recommend the service, while 95% of respondents said their consultation was either extremely helpful or very helpful, for a range of reasons including the sympathetic and knowledgeable nature of consultants.…”
Section: Perceptions Of Service Qualitysupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the positive perceptions of consultations services reported in previous research (Bell, 2000;Berry et al, 2012;O'Mahony et al, 2013), data gathered in this study pointed to highly positive perceptions of the consultations service. Questionnaire data showed 99% of 216 respondents stating they would recommend the service, while 95% of respondents said their consultation was either extremely helpful or very helpful, for a range of reasons including the sympathetic and knowledgeable nature of consultants.…”
Section: Perceptions Of Service Qualitysupporting
confidence: 92%
“…Operationally defined in this paper as formal, institutionally mandated one-to-one consultant-student teaching and learning interactions focusing on the development of written language or other key academic language and literacy or study skills, consultation services are found with increasing prevalence at higher education institutions across the globe (Hyland, 2018;Raforth, 2014). These services are delivered through writing centres (Harris, 2004, cited in Hoon, 2009Tiruchittampalam et al, 2017), university Academic Skills Centres (Berry et al, 2012), Learning Skills Units (Ma, 2019), within faculties and departments (Ma, 2019;O'Mahony, 2013) and through English Language Centres and other units (Author, 2019 unpublished survey).…”
Section: Introductionmentioning
confidence: 99%
“…An army of relevant studies are mainly focused on direct-indirect feedback (Wang, Wei, 2015;Li & Ye, 2016;Wei & Shi, 2016;Sarie, 2017) or global-local feedback (Yang & Wu, 2011;O'Mahony et al, 2013;Wang, 2016). In a bid to capture all existing types in written feedback, there is a necessity to incorporate both non-corrective and corrective feedback, including different types of the latter into research.…”
Section: Definition and Classification Of Feedbackmentioning
confidence: 99%
“…Some scholars argue against teacher feedback in the failure to offer speedy feedback (Bai, 2012), the negative result upon students to over-rely on their teachers and weaken their initiatives (Zhang, 2016). However, numerous empirical studies have indicated that teacher feedback helps students learn more and better (Chandler, 2003;Morch et al 2017), modify their essays towards greater grammatical accuracy, pragmatic appropriateness, complexity, clarity and comprehensibility (Li & Ye, 2016;Sarie, 2017), and thereby improve their writing competence (Wang & Liu, 2012;O'Mahony et al, 2013).…”
Section: Research Of Feedbackmentioning
confidence: 99%
See 1 more Smart Citation